1974
DOI: 10.1002/cne.901570107
|View full text |Cite
|
Sign up to set email alerts
|

Scanning electron microscopy of the subarachnoid space in the dog. II. Spinal nerve exits

Abstract: Young dogs were perfused with buffered aldehydes. For scanning electron microscopy MICROFIL was injected to help prevent vascular collapse. The dura-arachnoid was exposed leaving the nerve exits and rootlets intact. These were identified according to level and dissected free. Selected specimens were photographed at low magnification. Others were embedded in Epon 812 and sectioned for light and transmission electron microscopy. Similar specimens were prepared by critical point drying and palladium-gold coating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1977
1977
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Among other findings, ganglion neuronal cells were highly sensitive to transduction with IT‐administered AAV1 vector. This is probably the result of an anatomical feature of DRG in which many neural cell bodies are tightly packaged, as well as the lack of any morphologically detectable barriers 28–31. Dorsal root ganglion cells are important targets for treating several types of peripheral neuropathies, including intractable chronic pain 32, 33.…”
Section: Discussionmentioning
confidence: 99%
“…Among other findings, ganglion neuronal cells were highly sensitive to transduction with IT‐administered AAV1 vector. This is probably the result of an anatomical feature of DRG in which many neural cell bodies are tightly packaged, as well as the lack of any morphologically detectable barriers 28–31. Dorsal root ganglion cells are important targets for treating several types of peripheral neuropathies, including intractable chronic pain 32, 33.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the long structures extending from their origin at the spinal cord nearly to their passage through an intervertebral foramen are dorsal and ventral spinal roots, not spinal nerves. While the more caudally located dorsal and ventral roots may be enclosed by the same dural sheath, they are still distinct entities separated from each other by arachnoid membranes . One could incise the dural sheath and cleanly separate the dorsal, sensory roots from the ventral, motor roots.…”
mentioning
confidence: 99%
“…Previously the SEM had been used to describe the normal cytoarchitecture of spinal cord neurons and dorsal root ganglia (Siew, 19791, the spinal cord subarachnoid space (Cloyd and Low, 19741, spinal nerve root exits (Malloy and Low, 1974;Merchant, 19791, and the surface morphology of peripheral nerve and peripheral neuromas (Spencer and Lieberman, 1971). The morphology of degeneration and regeneration of peripheral nerves in the rat (Gershenbaum and Roisen, 1978) and rabbit (Orgel and Huser, 1980) and the morphology of axonal sprouts from cut dorsal root axons in the cat (Duce et al, 1976) have also been demonstrated by the SEM.…”
mentioning
confidence: 99%